Safeguarding Malaysia government audiovisual records: issues in collection management development / Nor Azah binti Hashim and Mazlina Pati Khan - Hashim, Nor Azah; Pati Khan, Mazlina (Faculty of Information Management, 2023)
The valuable audio-visual records created and produced by government agencies have the same high demand by researchers. This study was conducted to meet the objective of exploring the issues faced by government agencies in depositing valuable government Audio Visual (AV) records to the National Archives of Malaysia (NAM) as an information agency that is responsible for managing the reference sources. Five (5) selected government agencies purposely were inserted to obtain the data as a sample and population for the qualitative research design. Accordingly, the findings of the study have proposed six (6) strategies to be applied by government agencies to overcome the issues. The researcher opens this matter for future research.